Interactions between the Intrinsically Disordered Proteins β-Synuclein and α-Synuclein - Williams, Jonathan K. (Proteomics, 2018)
Several intrinsically disordered proteins (IDPs) have been implicated in the process of amyloid fibril formation in neurodegenerative disease, and developing approaches to inhibit the aggregation of these IDPs is critical for establishing effective therapies against disease progression. The aggregation pathway of the IDP alpha-synuclein (αS), is implicated in several neurodegenerative diseases known as synucleinopathies and has been extensively characterized. Less attention has been leveraged on beta-synuclein (βS), a homologous IDP that co-localizes with αS and is known to delay αS fibril formation. In this review, we focus on βS and the molecular-level interactions between αS and βS that underlie the delay of fibril formation. We highlight studies that begin to define αS and βS interactions at the monomer, oligomer, and surface levels, and suggest that βS plays a role in regulation of inhibition at many different stages of αS aggregation.